Coupled Deformation and Diffusion Process at the Stainless Steel/Carbon Steel Interface in the Deformation Bonding Process - Li, S.; Zhang, Q.D.; Liu, J.Y. (Проблемы прочности, 2018)
Cylindrical and surface-treated blanks were used to prepare stainless steel/carbon steel composite specimens at different temperatures. The coupled deformation and diffusion of materials at the interface were investigated by SEM and ultrasonic “C” scanning detection. The difference in the elongation of the two metals is shown to result in tearing at the interface in the deformation bonding process. Cracks are mainly located in a more readily expanding substrate and are more pronounced at lower deformation temperatures. With an increase in deformation temperatures, the bonding efficiency also increases significantly, but the diffusion layer thickness is basically the same. The bonding efficiency of composites can be greatly improved by mechanical surface treatment at normal deformation temperatures.